Anger as a mediator between peer victimization and deviant behavior in South Korea: a cross-cultural application of general strain theory - Oh, Gyeongseok (Crime & delinquency, 2019)
Little is known about the longitudinal effect of peer victimization on deviant behavior in non-Western cultural contexts and the mediating role of theoretically relevant variables, such as anger, on this association. The current study aimed to address this gap by analyzing data from a nationally representative sample of South Korean youth. Peer victimization was found to increase risk for anger and deviant behavior. Anger accounted for 27.06% of the total direct effect of peer victimization experienced during late childhood on deviant behavior during early adolescence. Results from the current study provide support for the cross-cultural application of general strain theory to help explain the longitudinal link between peer victimization and deviant behavior in a non-Western context such as South Korea.